2018
DOI: 10.2166/wst.2018.249
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of modified zeolites as adsorbents in wastewater treatment

Abstract: Natural zeolite has been recognized as a useful adsorbent for wastewater treatment for removing cations. Natural zeolite is a kind of porous material with large specific surface area but limited adsorption capacity. In recent years, emphasis has been given to prepare the surface modified zeolite using various procedures to enhance the potential of zeolite for pollutants. Modification treatment for zeolite can greatly change surface chemistry and pore structure. The article describes various modification method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 57 publications
0
46
0
2
Order By: Relevance
“…is newly fabricated composite polymer-zeolite showed great potential together with an effective capacity for the adsorption of gases like methane and carbon dioxide [112]. e fabrication of zeolites can be achieved by direct synthesis [113], sol gel method [114], or by a nonhydrothermal process [115,116].…”
Section: Conditionsmentioning
confidence: 99%
“…is newly fabricated composite polymer-zeolite showed great potential together with an effective capacity for the adsorption of gases like methane and carbon dioxide [112]. e fabrication of zeolites can be achieved by direct synthesis [113], sol gel method [114], or by a nonhydrothermal process [115,116].…”
Section: Conditionsmentioning
confidence: 99%
“…The advantages of chemical sorption methods include cost efficiency, availability of raw material base, high storage potential of new materials [6]. However, some sorbents described in scientific literature have essential disadvantsges, such as the impossibility of regeneration, instability to hostile environment, difficulties of automation of waste water detoxication [7]. A significant restriction to a wide use of some highly effective sorbents is the form of productiongranules or powder [8].…”
Section: Imentioning
confidence: 99%
“…Wang et al [10] synthesized Cr-doped TiO 2 supported zeolites in order to improve their structures, pore size, channels and absorption ability during photocatalytic activities [13,27,28]. Nyankson et al [12] also reported Zn (II) supported zeolite as the Zn-zeolite framework that generates a secondary pore; the secondary pore results larger surface area and has the ability to removal dyes, heavy metals, pesticides, and other pollutants from water [13,29]. erefore, this review explores the synthesis, characterization, and applications of zeolite [13,22,29].…”
Section: Introductionmentioning
confidence: 99%